Analisis Yuridis Normatif Hukum Islam terhadap Akad Jual Beli Melalui Media Sosial Facebook - Rayno Dwi Adityo; Aris Irawan (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
This study aims to find out the legal status of trading transaction agreement through facebook. Myang data source used consists of primary, secondary, and tertiary data sources. The method used to collect data by using literature study and field study. The results of this study indicate that the pattern of contract and form of expression (shigat) on the transaction on facebook is with the order from the consumer (muslam / aqid) which then the seller (muslam alaih / aqid) undertakes buyer's desire then there is a contract process with the agreed agreement together, ie each bound to exercise the rights and obligations (akad), then shigat form is when the seller undertakes the buyer's wish is called a statement (ijab) followed by a buyer's attitude statement to the goods to be purchased by paying the purchased item is called the answer (qobul). The position of the contract on this transaction is divided into two namely Shahih and Ghairu Shahih. This model transaction pattern is actually a processed creative innovation that developed from conventional traditional patterns to be more modern and practical.